Assessing the extent of non-aggressive cancer in clinically detected stage I non-small cell lung cancer. Issue 5 (20th October 2017) - Kale, Minal S; Sigel, Keith; Mhango, Grace; Wisnivesky, Juan P
Abstract : Background: Overdiagnosis among clinically detected lung cancers likely consists of cases that are non-aggressive and slowly progressive and will never disseminate, cause symptoms or be a threat to a subject's survival, even if untreated. In this study, we estimate the prevalence of non-aggressive lung cancers from a large, population-based cancer registry. Methods: We identified individuals ≥65 years with histologically confirmed, untreated stage I non-small cell lung cancers (NSCLCs) from the Surveillance, Epidemiology, and End Results-Medicare registry. We estimated the rate of non-aggressive lung cancers by determining the point at which the cumulative lung cancer-specific survival curve no longer changed (ie, the slope approaches zero). At this point, there are no additional deaths due to progressive lung cancer observed among untreated patients after adjusting for deaths from competing risks (these long-term survivors can be considered 'non-aggressive cases). Results: The overall rate of non-aggressive cancers among 2197 clinically detected cases of untreated stage I NSCLC was 2.4%, 95% CI: 1.0% to 3.8%. The rate of non-aggressive cancer was 1.9% (95% CI: 0.0% to 4.9%) for women and 2.4% (95% CI: 0.7% to 4.1%) for men (p=0.84). When stratifying by tumour size, non-aggressive cancer rates were 10.2% (95% CI: 0.0% to 29.3%), 2.1% (95% CI: 0.0% to 9.2%), 4.9% (95% CI: 0.0% to 10.3%), 1.8% (95% CI: 0.0% to 5.2%) and 0.0% (95% CI: 0.0% to 1.0%) for tumour sizes <15 mm, 15–24 mm, 25–34 mm, 35–44 mm and ≥45 mm, respectively. In comparison with the smallest tumour sizes (<15 mm), the rates of non-aggressive cancers were not statistically significantly different for tumour sizes 15–24 mm (p=0.36), 25–34 mm (p=0.57), 35–44 mm (p=0.38) and tumour sizes >45 mm (p=0.30). Discussion: We found relatively low rates of non-aggressive cancers among clinically detected, stage I NSCLC regardless of sex or size. Our findings suggest that most clinically diagnosed early stage cancers should be treated with curative intent.